GROWTH OF TOXOPLASMA GONDII (RH STRAIN) IN TWO DIFFERENT SPECIFIC-PATHOGEN-FREE STRAIN OF MICE - Z. Jawdat, S.; KH. Rifaat, L.; M. Kamel , Z. (The Iraqi Journal of Veterinary Medicine, 1990)
Specific-pathogen-free males Balb/c and C57 Black mice were inoculated intraperitoneally with different doses of Toxoplasma tachyzoites. The results showed that, mice inoculated with smaller dose gave maximum yields of tachyzoites at the time of death, and survived longer time than mice inoculated with larger dose.